Educational Values in the Presentation of Ma’dondi’ Music in Lembang Mai’ting (Catharsis, 2022)
Ma'dondi' music is the presentation of music used in the Ritual Rambu Solo' ceremony in Lembang Mai'ting, Rindingallo Sub-district. This study used descriptive qualitative methods. The data collection techniques included observation, interview, and documentation. This study aims to describe and analyze the educational value contained in the presentation of Ma'dondi' music in Lembang Mai'ting. Ma'dondi' is traditional music that must be maintained and preserved in the community because it can provide comfort, advice, and educational value that can be used as a way of life. The value of education in presenting Ma'dondi' music is obtained through the chanting of Ma'dondi' music poetry sung as oral literature. Be it the value of religious education, which aims to get closer to God; the value of social education, which aims to provide comfort to others and teach the meaning of caring and helping each other; the value of moral education, which aims to teach how to behave well; the value of aesthetic education, which aims to teach the beauty of giving and helping each other; and the value of cultural education, which aims to provide lessons that customs need to be maintained and preserved for future generations.